METHODIC APPROACHES TO ASSESSING THE INDIVIDUAL QUALITY OF LIFE OF COAL INDUSTRY WORKERS WITH OCCUPATIONAL DISEASES - Андрей Георгиевич Петров; Сергей Николаевич Филимонов; Виктор Андреевич Семенихин; Ольга Владимировна Хорошилова; Андрей Александрович Марьин; Вера Юрьевна Павлова (Медицина в Кузбассе, 2020)
The goal is to improve the quality of medical care for occupational diseases of the musculoskeletal system using non – steroidal anti-inflammatory drugs in the formation of health for employees of the coal industry.